(untitled) (Fiep Bulletin - online, 2013)
The Jiu-Jitsu is a sport that is in great rise and every day is gaining a larger number of supporters. Given its complexity, most coaches and trainers know the physiological characteristics and motor expressed during the fight, which predispose them to train their athletes empirically, based on knowledge and brought perpetuated for decades. Therefore the purpose of this research was to characterize the morphological and functional profile of an individual practitioner of Jiu-Jitsu that has significant results in state championships, national and global. This goal is justified by the few studies related to this issue and the fact that knowledge about the characteristics of practitioners struggle is essential for planning and adaptation to training. The research is featured as a case study. The individual is characterized male aged 26, who for 10 years practicing the sport and that figure as the world’s best in its class (Heavy) and among the top four in the world in absolute division (no weight limit ). The research instrument used was a semi-structured interview regarding training characteristics, anthropometric measurements and performance on tests of physical fitness (flexibility, strength / power of upper and lower limbs, strength / resistance and abdominal flexion of arm, horizontal and vertical jumping and aerobic capacity). From the results, it was found that the athlete study, presents with a high degree of performance, which shows that the athlete has high levels of qualification for high performance sport, featuring highly significant data for further comparative studies. The data revealed that the practice of Jiu-Jitsu requires a proper physical preparation for practitioners both nationally and internationally.